PROFIT MANAGEMENT ANALYSIS OF PROPERTY AND REAL ESTATE COMPANIES - Fyona Chelindiva; Maria Stefani Osesoga (Universitas Tidar, 2020)
This research aims to determine the effect of profitability, firm size, environment uncertainty, and growth opportunity towards earning management. By using the purposive sampling method, there were 43 companies listed in Indonesia Stock Exchange (IDX) from property, real estate, and building construction sectors for the period 2016-2018 used as samples. The results are profitability, firm size, environment uncertainty, and growth opportunity simultaneously has a significant effect on earnings management. Partially, profitability has a significant positive effect toward earning management, firm size and environment uncertainty has no positive effect toward earning management, and growth opportunity has no negative effect toward earning management.